2015
DOI: 10.1111/cars.12082
|View full text |Cite
|
Sign up to set email alerts
|

The Earnings and Employment Outcomes of the 2005 Cohort of Canadian Postsecondary Graduates with Disabilities

Abstract: Canada's fear of future skill and labor shortages has brought youth with disabilities to the forefront of public policy. Many universities are now reporting that an increased proportion of their graduating students identify as having a disability, and as a result, educational achievement-based programs designed to accommodate students' needs are growing across campuses. Despite recent attention by policymakers on improving accessibility standards and increasing employer incentives, young Canadians with disabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 48 publications
1
9
0
3
Order By: Relevance
“…Disability also shows a weak but statistically significant effect (p \ .10) when controlling for all other factors in Model 2. This finding resonates with recent research that found graduates with self-disclosed disabilities experience greater challenges in university and in making their transitions from school to work (see Zarifa, Walters, and Seward 2015).…”
Section: Discussionsupporting
confidence: 89%
“…Disability also shows a weak but statistically significant effect (p \ .10) when controlling for all other factors in Model 2. This finding resonates with recent research that found graduates with self-disclosed disabilities experience greater challenges in university and in making their transitions from school to work (see Zarifa, Walters, and Seward 2015).…”
Section: Discussionsupporting
confidence: 89%
“…It is important to recognize as well that many of the individual journeys taken by participants during their transition to adulthood included a description of their postsecondary education experience. An increasing number of individuals with disabilities are engaged with postsecondary education, and many of them are receiving advanced degrees (Zarifa, Walters, & Seward, ). Some of the journeys discussed above highlight individuals staying in school in order to meet other transition goals, such as leaving the family home.…”
Section: Discussionmentioning
confidence: 99%
“…26 People with disabilities have relatively low labor force participation, 4,5 even after completing higher education. 27 Unemployment or low income may have become stronger barriers to marriage among people with disabilities because of the growing emphasis on attaining economic stability before marrying. Further work is needed to understand if the accelerated retreat from marriage among people with disabilities is primarily due to economic disadvantages, or due to a recrudescence of stigma and discrimination.…”
Section: A N U S C R I P Tmentioning
confidence: 99%